2007
DOI: 10.1002/mc.20290
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 deficiency increases epidermal apoptosis and impairs recovery following acute UVB exposure

Abstract: The cyclooxygenases, COX-1 and COX-2, are involved in cutaneous responses to both acute and chronic UV exposure. In the present study, wild-type (WT), COX-1-/- and COX-2-/- mice were used to determine the influence of the individual isoform on mouse skin responses to acute UVB treatment. Immunohistochemistry and Western analysis indicated that COX-2, and not COX-1, was induced by UVB (2.5 or 5.0 kJ/m2), but that COX-1 remained the major source of prostaglandin E2 production. UVB exposure significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…We recently reported that the deficiency of COX-2 reduced UVB-induced PGE 2 levels by 35% and increased epidermal apoptosis compared with WT and COX-1À/À mice (24). Figure 1A shows an independent study comparing the levels of apoptosis in WT and COX-2À/À mice at 24 h after UVB exposure.…”
Section: Resultsmentioning
confidence: 96%
“…We recently reported that the deficiency of COX-2 reduced UVB-induced PGE 2 levels by 35% and increased epidermal apoptosis compared with WT and COX-1À/À mice (24). Figure 1A shows an independent study comparing the levels of apoptosis in WT and COX-2À/À mice at 24 h after UVB exposure.…”
Section: Resultsmentioning
confidence: 96%
“…These reports have shown that apigenin treatment downmodulates both basal and UVB-induced cyclooxygenase (COX)-2 expression in keratinocytes. A number of other laboratories have shown that selective COX-2 inhibition can reduce tumor formation (30)(31)(32)(33)(34), presumably by increasing apoptosis (35,36) in cells that have carcinogenic potential. A recent study by Akunda and colleagues (34) reported COX-2 deficiency significantly increased UVB-induced epidermal apoptosis, in agreement with previous findings by Tripp et al (32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, targeted Cox-2 gene deletion in myeloid cells does not modulate UVB skin tumor induction. (20). Pharmacologic studies also suggest that COX-2 plays a role in UVB-induced skin hyperplasia in SKH-1 hairless mice (21).…”
Section: Targeted Cox-2 Deletion In Skin Epidermal Cells Reduces Uvb mentioning
confidence: 99%